Means End Analysis (MEA) Model Development On Social Mathematics Learning Junior High School - Artika, Anggi (Journal of Innovation in Research, Education and Culture (JIREC), 2023)
The purpose of this development research was to produce a mathematics learning module using the Means End Analysis (MEA) model on the subject of Social Arithmetic for VII grade junior high school. The development model used is ADDIE only up to the stages of Analysis, Design, Development. The subject in this study was Expert Validation consisting of two Expert Lecturers and one Mathematics Teacher as validators. The feasibility of the mathematics learning module refers to the results of the module's assessment by experts on the learning module being developed. The mathematics learning module uses the Means End Analysis (MEA) model on the subject of Social Arithmetic which has been developed to meet the criteria of being feasible/valid to use for class VII junior high school students. Based on the results of expert validation, the results of the final assessment on IPPP-1 by the third expert with an average score of 3.53 with a proportion of 88.33% fulfilled the criteria. The results of the final assessment on IPPP-2 by the third expert with an average score of 3.92 with a proportion of 97.92% met the criteria. As well as the results of the final assessment on IPPP-3 by the third expert with an average score of 3.89 with a proportion of 97.22% fulfilling the criteria. Based on these data, it can be concluded that the development of mathematics learning modules using the means end analysis (MEA) model on the subject of social arithmetic in junior high school is feasible.Keywords: Development, Mathematics Learning Module, Social Arithmetic